Mortalin depletion induces MEK/ERK-dependent and ANT/CypD-mediated death in vemurafenib-resistant B-RafV600E melanoma cells. (1st April 2021) - Wu, Pui-Kei; Hong, Seung-Keun; Park, Jong-In
Abstract: Therapy resistance to a selective B-Raf inhibitor (BRAFi) poses a challenge in treating patients with BRAF -mutant melanomas. Here, we report that RNA interference of mortalin (HSPA9/GRP75), a mitochondrial molecular chaperone often upregulated and mislocalized in melanoma, can effectively induce death of vemurafenib-resistant progenies of human B-Raf V600E melanoma cell lines, A375 and Colo-829. Mortalin depletion induced death of vemurafenib-resistant cells at similar efficacy as observed in vemurafenib-naïve parental cells. This lethality was correlated with perturbed mitochondrial permeability and was attenuated by knockdown of adenine nucleotide translocase (ANT) and cyclophilin D (CypD), the key regulators of mitochondrial permeability. Chemical inhibition of MEK1/2 and ERK1/2 also suppressed mortalin depletion-induced death and mitochondrial permeability in these cells. These data suggest that mortalin and MEK/ERK regulate an ANT/CypD-associated mitochondrial death mechanism(s) in B-Raf V600E melanoma cells and that this regulation is conserved even after these cells develop BRAFi resistance. We also show that doxycycline-induced mortalin depletion can effectively suppress the xenografts of vemurafenib-resistant A375 progeny in athymic nude mice. These findings suggest that mortalin has potential as a candidate therapeutic target for BRAFi-resistant BRAF -mutant tumors. Highlights: Mortalin depletion effectively induces death of vemurafenib-resistant B-Raf V600E melanoma cells. This lethality is attenuated by knockdown of ANT and CypD, the key regulators of mitochondrial permeability. Inhibition of MEK1/2 and ERK1/2 suppresses mortalin depletion-induced death and mitochondrial permeability in these cells. ANT/CypD-associated mitochondrial death mechanism(s) is an Achilles heel in B-Raf inhibitor resistant melanomas cells.